Damage onset modeling in woven composites based on a coupled stress and energy criterion. (January 2017) - Doitrand, Aurélien; Fagiano, Christian; Carrère, Nicolas; Chiaruttini, Vincent; Hirsekorn, Martin
Abstract: The crack onset configuration at damage onset in a four-layer plain weave glass fiber/epoxy matrix composite is studied at the mesoscopic scale using a coupled criterion based on both a stress and an energy condition. The possible crack shapes are selected based on optical microscope observations of damage mechanisms on a specimen edge during a tensile test. The crack location, length and orientation, the decohesion length and the strain at damage onset are determined. The damage onset strain is underestimated compared to the experimental value determined by acoustic emission if only a stress criterion is considered. The coupled stress and energy criterion leads to a more reasonable estimate of strain at damage onset.